2021
DOI: 10.1111/add.15521
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and child genetic liability for smoking and caffeine consumption and child mental health: an intergenerational genetic risk score analysis in the ALSPAC cohort

Abstract: Background and aims Previous studies suggest an association between maternal tobacco and caffeine consumption during and outside of pregnancy and offspring mental health. We aimed to separate effects of the maternal environment (intrauterine or postnatal) from pleiotropic genetic effects. Design Secondary analysis of a longitudinal study. We (i) validated smoking and caffeine genetic risk scores (GRS) derived from published genome‐wide association study (GWAS) for use during pregnancy, (ii) compared estimated … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 60 publications
3
3
0
Order By: Relevance
“…Although in GenR and MoBa we found suggestive evidence for a causal relationship of maternal prenatal smoking on high risk of maternal‐reported ADHD symptoms, when comparing the findings across the cohorts, reporters and questionnaires the evidence was weak and inconsistent. Additionally, our PRS analyses with lifetime smoking PRS in ALSPAC and MoBa indicated pleiotropic associations which are consistent with recent findings in ALSPAC [54]. There is also a large body of evidence showing pleiotropy between smoking, impulsivity and sensation‐seeking type of personality [55, 56] which could confound observed phenotype associations in the present study.…”
Section: Discussionsupporting
confidence: 92%
“…Although in GenR and MoBa we found suggestive evidence for a causal relationship of maternal prenatal smoking on high risk of maternal‐reported ADHD symptoms, when comparing the findings across the cohorts, reporters and questionnaires the evidence was weak and inconsistent. Additionally, our PRS analyses with lifetime smoking PRS in ALSPAC and MoBa indicated pleiotropic associations which are consistent with recent findings in ALSPAC [54]. There is also a large body of evidence showing pleiotropy between smoking, impulsivity and sensation‐seeking type of personality [55, 56] which could confound observed phenotype associations in the present study.…”
Section: Discussionsupporting
confidence: 92%
“…Some (although not all) of these results were replicated in ALSPAC. Our results are in line with recent studies suggesting associations of increased smoking initiation PRS with increased risk-taking behaviours and decreased age at first birth, amongst other phenotypes [12,13,22]. However, we also found novel associations with other phenotypes not plausibly caused by smoking, suggesting that these potential pleiotropic effects may occur via a range of pathways.…”
Section: Discussionsupporting
confidence: 92%
“…However, subsequent studies have suggested that some of these SNPs may also be influencing different phenotypes via independent pathways (i.e., not via smoking). For example, in studies by Khouja and colleagues [12] and by Schellhas and colleagues [13],…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%
“…The study was a GWAS of a lifetime smoking index (which combined smoking initiation, duration, heaviness and cessation), conducted in a sample of 462,690 current, former and never smokers in UK Biobank [ 30 ]. A GRS based on the lifetime smoking GWAS has previously been shown to be associated with smoking behaviours during pregnancy in the ALSPAC cohort [ 31 ]. For the alcohol weighted GRS, there were 99 conditionally independent SNPs ( P < 5 × 10 −8 ), measured as the number of alcoholic drinks per week [ 32 ].…”
Section: Methodsmentioning
confidence: 99%